Coating with lycopene dye present in tomatoes as an alternative food supplementation (Research, Society and Development, 2024)
Lycopene is a carotenoid, a substance that gives tomatoes and other vegetables their red color, which stands out for being one of the most powerful antioxidants observed in research. It is also known as one of the best biological suppressors of free radicals, especially those derived from oxygen. This may be associated with a reduced risk of chronic diseases such as cardiovascular diseases and cancer, especially prostate and breast cancer, when adopting a diet based on tomatoes and derivatives rich in lycopene. In view of the above, the main objective of this research was to carry out a literature review on tomato microencapsulation and lycopene retention in different processes. With this study, a bibliographical survey was carried out between 2017 and 2023 of studies related to meta-analyses of lycopene microencapsulation. 27 review articles were found, three were eliminated after reading the abstract and 24 did not speak directly. It was verified that the objective of the work was fulfilled, considering that values considered relevant in the retention of this carotenoid after microencapsulation were presented, which makes its application a possible suggestion for better human nutrition.